Pemberian Pupuk Kandang Kambing dan Mikoriza untuk Meningkatkan Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) - Sri Wulandari; Aisyah Lubis; Erlita Chaniago (Jurnal Agrofolium, 2026)
This study used a Factorial Randomized Block Design with 2 factors studied and 3 replications where the first factor was goat manure (K) which consisted of 4 levels, namely K0 = (No Treatment), K1 = (1.5kg plot-1), K2 = (3kg plot-1). The second factor was mycorrhiza (M) which consisted of 3 levels, namely M0 = (No Treatment), M1 = (5g plant-1), M2 = (7.5g plant-1), M3 = (10g plant-1). The parameters observed were plant height (cm), number of pods containing per sample plant (pod), root volume per sample (ml), longest root length per sample (cm), weight of pods containing per plot (g), and weight of pods containing per sample plant (g). The results showed that the provision of goat manure had a very significant effect on the parameters of root volume per sample, the longest root length per sample, the number of filled pods per sample, the weight of filled pods per sample, and had a significant effect on the parameter of the weight of filled pods per plot. But it had no significant effect on the parameter of plant height. The provision of mycorrhiza had no significant effect on all observed parameters. The interaction of the provision of goat manure and mycorrhiza did not have a significant effect on all observed parameters.